2017
DOI: 10.7759/cureus.1861
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neurophysiological Intraoperative Monitoring during Spinal Cord and Spine Surgery: A Critical Analysis of 121 Cases

Abstract: Neuromonitoring has been utilized during spinal surgery to assess the function of the spinal cord in an effort to prevent intraoperative injury. Although its use is widespread, no clear benefit has been demonstrated. Our goal in this study was to interrogate the value of intraoperative neuromonitoring in decreasing the severity and rate of neurological injury during and after spinal surgery. Here we describe our experience of 121 patients who underwent spinal cord procedures with the combination of intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(26 reference statements)
0
10
0
2
Order By: Relevance
“…Ibrahim, et al studied 121 patients and concluded that neuromonitoring has a poor positive predictive value. They concluded it is an inappropriate test for preventing neurological injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ibrahim, et al studied 121 patients and concluded that neuromonitoring has a poor positive predictive value. They concluded it is an inappropriate test for preventing neurological injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Whether intraoperative neurophysiological monitoring may have changed outcome by enabling a more aggressive and sufficient surgical release is uncertain. [25][26][27] Nevertheless, axial pain in the back and pain in lower extremities seem to FIG. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Случай из практики стволов и сплетений определяют, стимулируя область расположения нервного ствола монополярным или биполярным зондом, т. е. осуществляя стимуляционную электромиографию [4][5][6]. Для получения достоверных результатов ИОНМ критически важно, чтобы во время проведения наркоза не применялись периферические миорелаксанты [7]. Опухоли позвоночника с паравертебральным прорастанием в полость грудной клетки встречаются относительно редко.…”
Section: Russian Journal Of Neurosurgeryunclassified
“…Статистика их распространенности отсутствует, а посвященные проблеме публикации ограничиваются описанием клинических случаев. Объемные образования такой локализации при гистологическом исследовании в большинстве случаев оказываются шванномами, берущими начало из блуждающего нерва [7,8]. Нередко они расположены недалеко от места прохождения диафрагмального нерва или же он пересекает саму опухоль [9].…”
Section: Russian Journal Of Neurosurgeryunclassified